Interaction of sugar stabilised silver nanoparticles with Momordica charantia seed lectin, a type II ribosome inactivating protein - Kenoth, Roopa; Sreekumar, Arya K; Sukanya, A.; Prabu, A. Anand; Kamlekar, Ravi Kanth (Glycoconjugate journal, 2023)
Sugar-stabilised nanomaterials have received a lot of attention in cancer therapy in recent years due to their pronounced application as specific targeting agents and maximizing their therapeutic potential while bypassing off-target effects. Lectins, the carbohydrate-binding proteins, are capable of binding to receptors present on the target cell/tissue and interact with transformed glycans better than normal cells. Besides some of the lectins exhibit anticancer activity. Conjugating sugar-stabilised NPs with lectins there for is expected to multiply the potential for the early diagnosis of cancer cells and the specific release of drugs into the tumor site. Because of the prospective applications of lectin-sugar-stabilised nanoparticle conjugates, it is important to understand their molecular interaction and physicochemical properties. Momordica charantia Seed Lectin (MCL) is a type II RIP and has been known as an anti-tumor agent. Investigation of the interaction between sugar-stabilised silver nanoparticles and MCL has been performed by fluorescence spectroscopy to explore the possibility of creating an effective biocompatible drug delivery system against cancer cells. In this regard interaction between lectin and NPs should be well-preserved, while recognizing the specific cell surface sugar. Therefore experiments were carried out in the presence and absence of specific sugar galactose. Protein intrinsic fluorescence emission is quenched at ~ 20% at saturation during the interaction without any significant shift in fluorescence emission maximum. Binding experiments reveal a good affinity. Tetrameric MCL binds to a single nanoparticle. Stern-Volmer analysis of the quenching data suggests that the interaction is via static quenching leading to complex formation. Hemagglutination experiments together with interaction studies in the presence of specific sugar show that the sugar-binding site of the lectin is distinct from the nanoparticle-binding site and cell recognition is very much intact even after binding to AgNPs. Our results propose the possibility of developing MCL-silver nanoparticle conjugate with high stability and multiple properties in the diagnosis and treatment of cancer.